Contribuições ao desenvolvimento do Projeto da Raia Virtual de Tiro da Marinha - Souza, Leonardo Cesar Cassiles de (2019)
Currently, the Brazilian Navy is facing difficulties to use specific areas in its real ammunition artillery exercises. These shooting training are specific to Naval Fire Support and require certain slope areas to bring them closer to reality. Such slopes are being increasingly restricted by several factors. Among these factors, we can mention the demographic expansion, which makes the use of slopes on the continent impossible and, mainly, for environmental protection, since the impact of munitions can cause damage to the environment. As a solution to these restrictions, we envisioned a Virtual Shooting Lane project capable of replacing the increasingly restricted and forbidden slopes for this purpose. That is, the design of the Virtual Shooting Lane aims to make the shooting place more flexible and avoid the use of island slopes, currently declared environmental reserves. The present work aims to develop an algorithm capable of indicating the location of a sound source generated by the impact of a projectile in the sea, using an acoustic buoy system and describe the general characteristics of the project of the Virtual Shooting Lane under development. This project makes a major contribution to the growth of the Defense Industry and the improving technological knowledge of the Navy, and also because it meets the need for a target shooting area for the execution of Naval Fire Support exercises. The development of this new technology will allow the continuity of the shooting exercises, previously performed only in Alcatrazes Island and, later, restricted to the Sapata Island, and its accomplishment in any point of the Brazilian jurisdictional waters, without temporal restriction.